2023
DOI: 10.3389/fimmu.2023.1069974
|View full text |Cite
|
Sign up to set email alerts
|

A combination of the HLA-DRB1*03 phenotype and low plasma mannose-binding lectin predisposes to autoantibody formation in women with recurrent pregnancy loss

Abstract: IntroductionIt is documented that a series of autoantibodies can be detected with increased frequency in women with recurrent pregnancy loss (RPL) and they may impact the pregnancy prognosis negatively. It is unknown whether the autoantibodies per se or the basic immune disturbances underlying autoantibody production, are the reason for this association. Our group has previously found that some genetically determined immunological biomarkers are associated with RPL and the same biomarkers are also in various d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 43 publications
(51 reference statements)
0
15
0
1
Order By: Relevance
“…The positive ( DRB1*04:01:01 and DRB1*08:01:01 ) and negative ( DRB1*07:01:01, DPB1*04:01:01; DPB1*14:01:01 ) class II alleles association with RPL suggest an at‐risk, or protective aspect to these alleles, respectively. This was in evident disagreement with studies on Brazilian, 47 Danish, 37,48 Japanese, 49 Kazakh, 40 and South Indian 25 women, which demonstrated the association of other DRB1 alleles with an increased risk of RPL, namely, DRB1*03:01:01 , and DRB1*07/*07 40,48 . This was further exemplified by the association of DRB1*03:01 with increased risk of RPL with a high risk of RPL in the (Central Asian) Kazakh subjects, 40 but not (Middle Eastern] Lebanese 5 or South European 33 populations.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…The positive ( DRB1*04:01:01 and DRB1*08:01:01 ) and negative ( DRB1*07:01:01, DPB1*04:01:01; DPB1*14:01:01 ) class II alleles association with RPL suggest an at‐risk, or protective aspect to these alleles, respectively. This was in evident disagreement with studies on Brazilian, 47 Danish, 37,48 Japanese, 49 Kazakh, 40 and South Indian 25 women, which demonstrated the association of other DRB1 alleles with an increased risk of RPL, namely, DRB1*03:01:01 , and DRB1*07/*07 40,48 . This was further exemplified by the association of DRB1*03:01 with increased risk of RPL with a high risk of RPL in the (Central Asian) Kazakh subjects, 40 but not (Middle Eastern] Lebanese 5 or South European 33 populations.…”
Section: Discussionmentioning
confidence: 74%
“…These findings were in line with findings on Lebanese 5 and Japanese 31 women with RPL but in disagreement with the findings of a French study which reported no link between DPB1 alleles and RPL. 54 These apparently inconsistent and conflicting find- of the production of target-specific antibodies, 37,51,57 and imbalance of proinflammatory-anti-inflammatory cytokine expression and activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, no difference between groups was found for the prevalence of the HLA-DRB1*07 phenotype, which suggests that these are not immunogenetic susceptibly markers for RPL. Thus, no immunogenetic susceptibility to RPL and only a weak immunogenetic susceptibility to autoimmunity in RPL patients could be found, and this may indicate that nongenetic factors play a more dominant role in RPL pathogenesis [4].…”
Section: English Summarymentioning
confidence: 94%